Method of network slicing deployment based on performance-aware - Kaizhi HUANG; Qirun PAN; Quan YUAN; Wei YOU; Hongbo TANG (Tongxin xuebao)
In order to deal with the performance degradation caused by resource contention due to the sharing of physical resources between VNF in the network slicing,a network slicing deployment method based on performance-awareness was proposed.When deploying network slice instances,first two-phase deployment that mapping virtual nodes was adopted,and then virtual links were mapped.In the virtual nodes mapping phase,the VNF performance influences factor was defined from the perspective of resource supply and demand to quantify the degree of VNF performance impact.Then the sum of the performance influence factors of all VNF on the deployable physical server was found in the network slice instance,the physical server with the smallest sum of performance influence factors was used as the mapping location,and the simulated annealing-discrete particle swarm algorithm was used to find the nodes mapping result.In the virtual links mapping phase,the shortest path algorithm was used to obtain the link mapping result.The simulation results show that the proposed method reduces the impact of other network slices on its own service performance.